1999
DOI: 10.1007/bf02562278
|View full text |Cite
|
Sign up to set email alerts
|

Cellular fatty acid transport in heart and skeletal muscle as facilitated by proteins

Abstract: Despite the importance of long-chain fatty acids (FA) as fuels for heart and skeletal muscles, the mechanism of their cellular uptake has not yet been clarified. There is dispute as to whether FA are taken up by the muscle cells via passive diffusion and/or carrier-mediated transport. Kinetic studies of FA uptake by cardiac myocytes and the use of membrane protein-modifying agents have suggested the bulk of FA uptake is due to a protein component. Three membrane-associated FA-binding proteins were proposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
72
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 47 publications
6
72
0
1
Order By: Relevance
“…Approximately a third of the improved delivery of fatty acids to bird muscles could be related to their small fiber size and high capillary surface density; however, most of the improved delivery of fatty acids is likely to be due to changes in protein-mediated transport (Guglielmo et al, 2002a). The bulk of fatty acid transport across the sarcolemma is mediated by proteins, including fatty acid translocase (FAT/CD36) and plasma membrane fatty acid binding protein (FABPpm), and high intracellular concentrations of the heart-type fatty acid binding protein (H-FABP) promote rapid uptake, movement and disposal of fatty acids (Luiken et al, 1999;Sweazea and Braun, 2006). Pectoralis muscles of migrating western sandpipers have an approximately 10-fold greater concentration of H-FABP (up to 11% of cytosolic protein) than that of mouse soleus muscle, and H-FABP has been shown to increase by 70% during migratory seasons compared with winter (Guglielmo et al, 2002a).…”
Section: Meeting the Challenge Of Fat-fueled Flightmentioning
confidence: 99%
“…Approximately a third of the improved delivery of fatty acids to bird muscles could be related to their small fiber size and high capillary surface density; however, most of the improved delivery of fatty acids is likely to be due to changes in protein-mediated transport (Guglielmo et al, 2002a). The bulk of fatty acid transport across the sarcolemma is mediated by proteins, including fatty acid translocase (FAT/CD36) and plasma membrane fatty acid binding protein (FABPpm), and high intracellular concentrations of the heart-type fatty acid binding protein (H-FABP) promote rapid uptake, movement and disposal of fatty acids (Luiken et al, 1999;Sweazea and Braun, 2006). Pectoralis muscles of migrating western sandpipers have an approximately 10-fold greater concentration of H-FABP (up to 11% of cytosolic protein) than that of mouse soleus muscle, and H-FABP has been shown to increase by 70% during migratory seasons compared with winter (Guglielmo et al, 2002a).…”
Section: Meeting the Challenge Of Fat-fueled Flightmentioning
confidence: 99%
“…9 Because of the hydrophobic nature of NEFA, it has generally been assumed that they can rapidly traverse the lipid bilayer of the cell membrane by their mass action. However NEFA may also enter the cell via a carrier-mediated process in many cells, including cardiac myocytes 10 and adipocytes. 11 FAT=CD36 is a transmembrane transporter of long-chain fatty acids, 12 which in turn have been shown to upregulate the fatty acid translocase itself.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is accumulating that cellular LCFA uptake is a rate-governing step in LCFA utilization (10). Using heart giant membrane vesicles, a model used to investigate cardiac LCFA uptake dissected from LCFA metabolism (11) and cardiac myocytes, in which LCFA uptake is closely linked to metabolism (12), we previously showed that ϳ50% of cardiac LCFA uptake is mediated by the 88-kDa putative LCFA transport protein, fatty acid translocase (FAT)/CD36.…”
mentioning
confidence: 99%